Shari’ah in the English Courts: Towards a New theory of Convergence of Laws in England - Sodiq Olalekan Omoola; Maruf A. Nasir (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2020)
In the birth place of Common law, there is an emerging paradigm shift in the attitude of English courts towards Islamic law principles fromcheer hostility in the colonial era towards to modern convergence. This situation might be as a result of the heterogeneous nature of contemporary British societies, with its growing immigrant and religious communities, and their quest for an effective dispute resolution mechanism suitable for their religion and satisfy their cultural sensitivities. This paper seeks to examine the general attitude of English courts towards religious courts and tribunals, particularly the current state of convergence between Common Law and Shari’ah in England and Wales.The role of the UK Arbitration Act 1996 and English case law in regulating religious arbitration and the natural convergence established in recent years in England is also analyzed.The paper finds that developments in recent years including the proliferation of Muslim Tribunals in England has herald a new theory of convergence of Shari’ah Law and Common Law in the aspect of  Family Law and Marriage in contemporary English courts. This has contributed to reshape the evolution and relationship between these two major world Legal systems.